What Is Translational Research? Concepts and Applications in Nutrition and Dietetics - Zoellner, J.; Van Horn, L.; Gleason, P.; Boushey, Carol (Elsevier, 2015)
This monograph is tenth in a series of articles focused on research design and analysis, and provides an overview of translational research concepts. Specifically, this article presents models and processes describing translational research, defines key terms, discusses methodological considerations for speeding the translation of nutrition research into practice, illustrates application of translational research concepts for nutrition practitioners and researchers, and provides examples of translational research resources and training opportunities. To promote the efficiency and translation of evidence-based nutrition guidelines into routine clinical-, community-, and policy-based practice, the dissemination and implementation phases of translational research are highlighted and illustrated in this monograph.